METHODOLOGICAL PRINCIPLES OF EDUCATIONAL AND PSYCHOLOGICAL CHATBOT DEVELOPMENT - Vitaliy Panok; Anatoliy Shevchenko; Maksym Nazar; Denys Starkov; Dmytro Meshcheriakov; Andriy Shevtsov (Інформаційні технології і засоби навчання)
The study aims to describe the methodology for developing educational and psychological chatbots, covering its key principles, features, and stages. Educational and psychological chatbots are defined as those that provide conditions for psychological (self-)help and teach users more effective thinking and activity strategies, facilitating the acquisition of new knowledge, skills, and abilities. The main objectives of the study include the analysis of modern scientific sources to clarify methodological approaches to the development of educational and psychological chatbots, identifying their psychological and educational functions, and studying aspects of their implementation in various practical fields. Additionally, the study summarizes personal experience in participating in Ukrainian scientific and practical teams involved in developing relevant solutions and the interpretation, systematization, and comprehension of the obtained results. As a result of the conducted research, methodological principles for the development of educational and psychological chatbots using artificial intelligence technologies have been established. These principles include empirical justification and effectiveness assessment, personalization of user interactions, adherence to ethical principles (protection of users' life, health, and well-being, ensuring their confidentiality, ensuring the accuracy and objectivity of the provided information), accessibility and scalability, interactivity, interdisciplinary approach, integration of new technologies and approaches, and testing. A general algorithm for the development of educational and psychological chatbots, consisting of 8 stages, has been prepared. Scientifically based development and societal implementation of educational and psychological chatbots using artificial intelligence technologies unlocks significant potential for improving the quality of life and strengthening users' psychological well-being. This opportunity is particularly relevant for Ukraine in the context of full-scale war and post-war recovery. In-depth scientific research and interdisciplinary support in the issues of revealing and implementing ethical principles of chatbot functioning, such as user safety, privacy protection, and ensuring the certainty and objectivity of the provided information, are of priority importance.